Investigation of models of the yarn-bobbin drying process by determination of their parameters using genetic algorithm. Issue 10 (June 2017) - Susantez, Çiğdem; Hacıhafızoğlu, Oktay; Kahveci, Kamil
In the first part of this study, the drying behavior of wool-acrylic yarn bobbins was investigated by a theoretical model and genetic algorithm method. Each candidate solution for Do, D 1 and D 2 was presented on a single chromosome. The values of Do, D 1 and D 2 yielding the best fit between the experimental and predicted moisture contents were obtained using the genetic algorithm. In the second part of this study, the suitability of various empirical and semiempirical models in the modeling of the drying process was investigated by the genetic algorithm. The population number was taken as 30 and the tournament selection method was used. The calculations were performed until the 20th generation for the theoretical model and 100th generation for the empirical and semiempirical models. The results show that the genetic algorithm can be successfully used in the modeling of the drying process of yarn bobbins. The results also show that the Verma et al. and Diffusion Approach models yield the best fit with experimental data.